The truth about the Mahaweli - Iriyagolle, Gamini (On the irrigation and hydro-electric development project using the waters of the Mahaweli, longest river in Sri Lanka., 1978)
On the irrigation and hydro-electric development project using the waters of the Mahaweli, longest river in Sri Lanka.